Recent Developments in Biomaterial-Based Hydrogel as the Delivery System for Repairing Endometrial Injury - Cai, Guiyang; Hou, Zhipeng; Sun, Wei; Li, Peng; Zhang, Jinzhe; Yang, Liqun; Chen, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Endometrial injury caused by intrauterine surgery often leads to pathophysiological changes in the intrauterine environment, resulting in infertility in women of childbearing age. However, clinical treatment strategies, especially for moderate to severe injuries, often fail to provide satisfactory therapeutic effects and pregnancy outcomes. With the development of reproductive medicine and materials engineering, researchers have developed bioactive hydrogel materials, which can be used as a physical anti-adhesion barrier alone or as functional delivery systems for intrauterine injury treatment by loading stem cells or various active substances. Studies have demonstrated that the biomaterial-based hydrogel delivery system can provide sufficient mechanical support and improve the intrauterine microenvironment, enhance the delivery efficiency of therapeutic agents, prolong intrauterine retention time, and perform efficiently targeted repair compared with ordinary drug therapy or stem cell therapy. It shows the promising application prospects of the hydrogel delivery system in reproductive medicine. Herein, we review the recent advances in endometrial repair methods, focusing on the current application status of biomaterial-based hydrogel delivery systems in intrauterine injury repair, including preparation principles, therapeutic efficacy, repair mechanisms, and current limitations and development perspectives.